Public Health in the Middle East and North Africa : Meeting the Challenges of the Twenty-first Century - Pierre-Louis, Anne Maryse; Akala, Francisca Ayodeji; Karam, Hadia Samaha (Washington, DC: World Bank, 2013)
This report documents the main highlights and findings from the Middle East Regional Symposium, "Meeting the Public Health Challenges of the 21st Century in the Middle East and North Africa/Eastern Mediterranean Region", held in Beirut in June 2002. The Middle East and North Africa (MENA) region is currently undergoing both epidemiological and demographical transitions which are resulting in changing patterns of mortality and morbidity. Chronic and non-communicable diseases and injuries now account for a growing share of the overall burden of ill health. Countries of the region are faced with the challenge of addressing these emerging issues while, at the same time trying to complete the unfinished agenda of addressing diseases and protecting the health of mothers and children. The book consists of an overview drawing on a broad range of presentations at the conference, followed by chapters on specific public health issues including: functions and infrastructures, choosing and financing public health services, public health best buys, health promotion, HIV/AIDs, road safety, and strengthening primary health care.